La Croissance Urbaine au Zaire - De Muynck, M.T. Lootens (Afrika Focus, 1987)
The present paper retraces the hierarchy of the most important centers of Zaïre on the dates of 1956, 1970 and 1984. The distribution of the "rank and size rule" is log-normal in the colonial period and primate in the post-colonial period. The primacy of Kinshasa is growing in the last decennia, shown by the calculation of the "two-city and the five-city primacy index". In all the cities with the exception of Kolwezi, the strong demographic growth during the sixties and the early seventies has been slowed at present. Even in some cities the early famous rural versus urban migration became a mere story. KEYWORDS: population, urban geography, urbanization, Zaïre